Assessment of Obstetric and Neonatal Health Services in Developing Country Health Facilities - Manasyan, Albert (2013)
OBJECTIVE: To describe the staffing and availability of medical equipment and medications and the performance of procedures at health facilities providing maternal and neonatal care at African, Asian, and Latin American sites participating in a multicenter trial to improve emergency obstetric/neonatal care in communities with high maternal and perinatal mortality. STUDY DESIGN: In 2009, prior to intervention, we surveyed 136 hospitals and 228 clinics in 7 sites in Africa, Asia, and Latin America regarding staffing, availability of equipment/medications, and procedures including cesarean section. RESULTS: The coverage of physicians and nurses/midwives was poor in Africa and Latin America. In Africa, only 20% of hospitals had full-time physicians. Only 70% of hospitals in Africa and Asia had performed cesarean sections in the last 6 months. Oxygen was unavailable in 40% of African hospitals and 17% of Asian hospitals. Blood was unavailable in 80% of African and Asian hospitals. CONCLUSIONS: Assuming that adequate facility services are necessary to improve pregnancy outcomes, it is not surprising that maternal and perinatal mortality rates in the areas surveyed are high. The data presented emphasize that to reduce mortality in these areas, resources that result in improved staffing and sufficient equipment, supplies, and medication, along with training, are required.